2015
DOI: 10.2495/air150341
|View full text |Cite
|
Sign up to set email alerts
|

Transport tax in Russia as a promising tool for the reduction of airborne emissions and the development of the road network

Abstract: This paper focuses on the fact that Russia is to see an accelerated and unregulated growth of the car fleet, while the development of the road network is seriously lagging behind. The paper looks at the theoretical aspects of the internalization of transport externalities and analyzes negative externalities of car use. It characterizes the key negative impacts that potentially need to be offset through transport tax. It is proved that the impacts are most prominent in areas with a higher rate of car ownership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
3
Order By: Relevance
“…The study on the impact of emerging next-generation vehicles with smart vehicle technologies on the vehicle market [9] revealed that the cars using conventional motor fuels would keep their current position. The problem of the ecological danger of fuels and their combustion products requires one to look for integrated solutions, including new approaches in car and engine constructions [10]; improving the technological parameters of transport, with emphasis on multi-material construction for weight reduction [11]; increasing the adaptability of vehicles to operating conditions [12], in particular under weather changes [13], with application of such instruments as the dynamic vehicle scheduling [14]; tightening international and national requirements for fuel quality [15][16][17], use of tax instruments [3,[18][19][20][21]. Limited possibilities for improving the quality of motor fuels by refining methods [22][23][24] necessitate the use of fuel additives of various purposes, the combination of which in small amounts ensures the environmental and operational characteristics achieve the desired level [25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…The study on the impact of emerging next-generation vehicles with smart vehicle technologies on the vehicle market [9] revealed that the cars using conventional motor fuels would keep their current position. The problem of the ecological danger of fuels and their combustion products requires one to look for integrated solutions, including new approaches in car and engine constructions [10]; improving the technological parameters of transport, with emphasis on multi-material construction for weight reduction [11]; increasing the adaptability of vehicles to operating conditions [12], in particular under weather changes [13], with application of such instruments as the dynamic vehicle scheduling [14]; tightening international and national requirements for fuel quality [15][16][17], use of tax instruments [3,[18][19][20][21]. Limited possibilities for improving the quality of motor fuels by refining methods [22][23][24] necessitate the use of fuel additives of various purposes, the combination of which in small amounts ensures the environmental and operational characteristics achieve the desired level [25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…В табл. 1 нами представлена характеристика основных отрицательных эффектов от использования автотранспорта, которые потенциально нуждаются в компенсации через транспортное обложение [Mayburov, Leontyeva, 2015а;].…”
Section: анализ эффектов связанных с форсированной автомобилизациейunclassified
“…Table presents the characteristics of the key negative externalities of car use that need to be corrected through transport tax. It has to be noted that the presented externalities are the ones that are most apparent at a higher rate of car ownership when a considerable part of the population of a territory develops strong automobile dependency [13][14][15].…”
Section: Analysis Of Effects Relating To Accelerated Motorizationmentioning
confidence: 99%